2015
DOI: 10.1038/srep16932
|View full text |Cite
|
Sign up to set email alerts
|

Dual transcriptome sequencing reveals resistance of TLR4 ligand-activated bone marrow-derived macrophages to inflammation mediated by the BET inhibitor JQ1

Abstract: Persistent macrophage activation is associated with the expression of various pro-inflammatory genes, cytokines and chemokines, which may initiate or amplify inflammatory disorders. A novel synthetic BET inhibitor, JQ1, was proven to exert immunosuppressive activities in macrophages. However, a genome-wide search for JQ1 molecular targets has not been undertaken. The present study aimed at evaluating the anti-inflammatory function and underlying genes that are targeted by JQ1 in LPS-stimulated primary bone mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 60 publications
4
23
0
Order By: Relevance
“…To date, few studies have described the autophagy‐modulating role of BRD4 inhibition in tumour cells . One such study reported that glioma cells treated with JQ1 exhibited increased autophagic activity . In imatinib‐resistant GIST cells, increased expression of LC3‐II, a widely accepted autophagic marker, was inducible by JQ1, and its level was even higher upon combined treatment with JQ1 and imatinib.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, few studies have described the autophagy‐modulating role of BRD4 inhibition in tumour cells . One such study reported that glioma cells treated with JQ1 exhibited increased autophagic activity . In imatinib‐resistant GIST cells, increased expression of LC3‐II, a widely accepted autophagic marker, was inducible by JQ1, and its level was even higher upon combined treatment with JQ1 and imatinib.…”
Section: Discussionmentioning
confidence: 99%
“…44 One such study reported that glioma cells treated with JQ1 exhibited increased autophagic activity. [45][46][47] In imatinib-resistant GIST cells, increased expression of LC3-II, a widely accepted autophagic marker, was inducible by JQ1, and its level was even higher upon combined treatment with JQ1 and imatinib. Although AKT-inactivation-induced apoptosis directs cells to programmed death, the significance of BRD4-inhibitioninduced autophagy in GIST requires further elucidation.…”
Section: Discussionmentioning
confidence: 99%
“…Then, peritoneal macrophages were plated in plates or dishes and cultured at 37 °C in a humidified incubator supplemented with 5% CO2. Murine bone marrow-derived macrophages (BMDMs) were isolated from the femurs of BALB/c mice and differentiated by supplementing with 50 ng/ml m-CSF for 3–5 days40. Primary macrophages or murine macrophage such as RAW 264.7 cells (ATCC, Manassas, VA, USA) were cultured in high-glucose DMEM supplemented with 10% FBS at 37 °C in a 5% CO2 humidified incubator.…”
Section: Methodsmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study exploring the role of BRD4 in inflammatory response regulation after SCI and describing a BRD4 inhibitor capable of suppressing inflammatory response via negatively modulating NF-κB and MAPK signalling pathways (Figure 8).BET family such as BRD4 are reported to activate many inflammation-related genes,26 and inflammation blocks functional recovery and aggravates neuropathic paresthesia in damaged spinal cord 27,28. To the best of our knowledge, this is the first study exploring the role of BRD4 in inflammatory response regulation after SCI and describing a BRD4 inhibitor capable of suppressing inflammatory response via negatively modulating NF-κB and MAPK signalling pathways (Figure 8).BET family such as BRD4 are reported to activate many inflammation-related genes,26 and inflammation blocks functional recovery and aggravates neuropathic paresthesia in damaged spinal cord 27,28.…”
mentioning
confidence: 99%